2022
DOI: 10.1101/2022.01.25.22269811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of HBV and HCV transmission in multi-transfused Thalassemia patients of Azad Jammu and Kashmir, Pakistan

Abstract: Background: Thalassemia patients need regular blood transfusion which saves their lives but increases the risk of acquiring viral infections like hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV). Objective(s): This study aimed to screen out the HCV and HBV infections in Thalassemia patients receiving regular blood in three centers of Azad Jammu and Kashmir (AJK), Pakistan. Materials and Methods: It was a cross sectional, multicenter study involving 224 Thalassemia patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Pakistan has a high prevalence of HBV infection, which varies between provinces. Several recent studies from the year 2021–22 showed a high prevalence of HBV infection (detected either through a positive PCR or positive HBsAg serum test) in adults varying from 80% in Sindh ( Jamali, 2022 ), 50% in Khyber Pakhtunkhwa ( Muhammad et al, 2022 ), 65% in Punjab ( Raza et al, 2022 ), 17% in Baluchistan ( Sheikh et al, 2011 ) and 28.1% in Azad Jammu and Kashmir ( Mahmood et al, 2022 ). Epidemiological studies have focused predominantly on people who inject drugs and incarcerated individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan has a high prevalence of HBV infection, which varies between provinces. Several recent studies from the year 2021–22 showed a high prevalence of HBV infection (detected either through a positive PCR or positive HBsAg serum test) in adults varying from 80% in Sindh ( Jamali, 2022 ), 50% in Khyber Pakhtunkhwa ( Muhammad et al, 2022 ), 65% in Punjab ( Raza et al, 2022 ), 17% in Baluchistan ( Sheikh et al, 2011 ) and 28.1% in Azad Jammu and Kashmir ( Mahmood et al, 2022 ). Epidemiological studies have focused predominantly on people who inject drugs and incarcerated individuals.…”
Section: Introductionmentioning
confidence: 99%